Media Perceptions on Press Council Regulation of AI in Journalism Practice - Anggi Oktarinda; Eni Maryani; Pandan Yudhapramesti; Andika Vinianto Adiputra (UPT Publikasi Ilmiah UNISBA, 2025)
Press Council Regulation No. 1 of 2025 concerning Guidelines for the Use of Artificial Intelligence in Journalistic Works marks a significant initial measure in ensuring that technological advancements do not undermine the fundamental journalistic principles in Indonesia. It reflects the nation’s commitment to preserving press integrity and ethical standards in the context of rapid AI adoption. This study examines the digital media’s perceptions and responses towards these guidelines in the early stages of their dissemination. Employing a descriptive qualitative method, the research utilizes case studies of Ayo Media Network—a network-based digital platform—and Bisnis Indonesia—a segmented newspaper expanding into digital media. Data were obtained through interviews, observations, and document analysis. The findings reveal that digital media practitioners accepted the Guidelines, acknowledging their relevance, urgency, and alignment with the ongoing media industry’s digital transformation. In response, media organizations intend to realign their practices with these Guidelines to safeguard journalistic integrity and public trust. The principal challenge lies in the aspect of translating principles into practice, as well as institutional support to strengthen the internalization of ethical values. Strengthened socialization, coaching, and stakeholder collaboration are essential to establish these Guidelines as a foundational framework for responsible AI-driven journalism in Indonesia.